Archean Iron-Based Metabolism Analysis and the Photoferrotrophy-Driven Hypothesis of Microbial Magnetotaxis Origin. Issue 3 (16th March 2019) - Strbak, Oliver; Dobrota, Dusan
Abstract: Despite its biological and geological significance, the origin of microbial magnetosome biomineralization, as well as the evolution of magnetotaxis, is still not well understood. Recently, the origin of magnetotaxis has been proposed to already exist in the Archean Eon. However, the Archean environment was fully anoxic. Therefore, what was the reason for the evolution of magnetotaxis in the anoxic Archean ocean and what mechanism could lead to the formation of single domain-sized magnetite nanoparticles that are a necessary condition of magnetotaxis functionality? Since the genetically controlled magnetosomes formation is extremely energetically demanding, in this review, we analyze Archean anoxic iron-based metabolism and we delineate the alternative possibilities of non-genetically controlled magnetosomes precursor origin as a necessary condition of magnetotaxis emergence. We show that coupling of anoxygenic photosynthesis with ferrous iron as an electron donor, with anaerobic respiration with ferric iron as an electron acceptor, provided sufficient material for non-genetically controlled magnetite formation. The co-evolution of cyanobacteria is suggested as the possible environmental pressure responsible for the emergence of Archean magnetotaxis. In accordance with the hypothesis of the reactive oxygen species-protective function of the first magnetosomes, we show that the formation of single domain-sized magnetite nanoparticles did not have to be initially connected with magnetotaxis origin, neither had to be genetically controlled nor intracellular. Instead, it could result from the long-lasting ambient pressure of metabolically produced extracellular iron oxide minerals in photoferrotrophs together with the emergence of local oxygen oases. The presence of oxygen could favor cells with the ability to navigate into oxic-anoxic transition zones since the oxygen was entirely toxic to Archean life. This evolutionary advantageous trait could finally result in a niche construction origin of genes responsible for intracellular magnetosome formation, which have remained preserved until today.